Efek Aplikasi Kombinasi Urea dan Pupuk Hayati Inokulum Rhizobium terhadap Pertumbuhan dan Hasil Tanaman Kedelai (Glycine Max (L.) Varietas Derap 1 - Ahmad Sholeh; Nurhidayati Nurhidayati (Universitas Islam Malang, 2021)
The productivity of the national soybean crop is still relatively low, namely 1.44-1.56 tons ha-1, so it has not been able to meet the needs of the community which reaches 3 million tons. Therefore, efforts are needed to increase soybean productivity with a more efficient cultivation system. This study aims to determine the response to growth and yield of soybeans of Derap 1 variety resulting from the interaction of urea and Rhizobium inoculum. This study used a randomized block design. The first factor: the dose of urea fertilizer (20.30 kg ha-1) The second factor is the dose of biological fertilizer inoculum Rhizobium (0, 2, 4, 6 g kg-1) seeds. The results showed that there was a significant interaction effect between the treatment dose of urea fertilizer and the dose of biological fertilizer Rhizobium inoculum. U3H3 treatment (Urea 30 kg ha-1+ Rhizobium inoculum 6 g kg-1 seeds) gave the highest growth as measured by plant height (39.00 cm), number of leaves (14.40 stalks), number of branches (4.00 cm). ), the amount of interest (86.77). This treatment also gave the highest yield as measured by the number of harvested pods (54.60), dry weight of pods (48.80 g), dry weight of seeds per plant (29.24 g), dry weight of seeds per ha (2.52 tons). ha-1)